The performace of estevia crops transplanted in diferent densities and double spacing - Carneiro, José Walter Pedrosa; Martins, Elias Nunes; Guedes, Terezinha Aparecida; Silva, Maria Aparecida G. D. da (Pesquisa Agropecuaria Brasileira, 1992)
This experiment was carried out during two years to evaluate the performance of Stevia (Stevia rebaudiana (Bert.) Bertoni) crops in three densities of transplanting per hectare in two double spacing and a control. The higher yield of pure seed germinating per hectare in the first year was obtained with 79.000 transplants per hectare. There was no influence of densities of transplants in the yield of leaves, in the first year. The highest yield of pure seed germinating was obtained with 80.000 transplants per hectare, and, lowest yield of leaves with 50.000 and 80.000 transplants in double spacing of 35 per 65 centimeters. Densities lower than 100.000 transplants per hectare in double spacing had lower yield than had the control. The best fit was obtained with the reciprocal model.